2012
DOI: 10.1016/j.taap.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

3,3′-Diindolylmethane, but not indole-3-carbinol, inhibits histone deacetylase activity in prostate cancer cells

Abstract: Increased consumption of cruciferous vegetables is associated with a reduced risk of developing prostate cancer. Indole-3-carbinol (I3C) and 3,3′-diindolylmethane (DIM) are phytochemicals derived from cruciferous vegetables that have shown promise in inhibiting prostate cancer in experimental models. Histone deacetylase (HDAC) inhibition is an emerging target for cancer prevention and therapy. We sought to examine the effects of I3C and DIM on HDACs in human prostate cancer cell lines: androgen insensitive PC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 44 publications
1
41
0
4
Order By: Relevance
“…Several naturally occurring anticancer phytochemicals have been shown to possess the ability to prevent cancer via epigenetic modifications (14,15,(39)(40)(41). A previous study showed that DIM possesses the ability to inhibit HDAC activity which correlated with increased expression of p21in both human PC-3 and LNCaP cells (19). However, no study has been reported so far on the potential epigenetic modifications, and the anticancer efficacy of DIM in a transgenic prostate cancer mouse model such as TRAMP mice remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several naturally occurring anticancer phytochemicals have been shown to possess the ability to prevent cancer via epigenetic modifications (14,15,(39)(40)(41). A previous study showed that DIM possesses the ability to inhibit HDAC activity which correlated with increased expression of p21in both human PC-3 and LNCaP cells (19). However, no study has been reported so far on the potential epigenetic modifications, and the anticancer efficacy of DIM in a transgenic prostate cancer mouse model such as TRAMP mice remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our laboratory showed that curcumin, a potent anticancer agent against many cancers such as prostate cancer, suppresses DNA methyltransferases (DNMT) expression and modifies the histone deacetylases (HDAC) activity in human prostate LNCaP cells, which might contribute to DNA demethylation in promoter region of Nrf2 gene in TRAMP-C1 cells as well as Neurog1 gene in LNCaP cells (14,15). 3,3′-diindolylmethane (DIM), a compound derived from indole-3-carbinol (I3C), is found abundantly in cruciferous vegetables and its multi-target anticancer and cancer chemopreventive effects have been demonstrated in many in vivo and in vitro cancer models (16)(17)(18)(19). Currently, there are around ten clinical trials being conducted in early stage of prostate, breast, and cervical cancer patients for this compound (www.clinicaltrial.gov).…”
Section: Introductionmentioning
confidence: 99%
“…In PC-3 and LNCaP cells, DIM markedly reduced HDAC2 activity causing increase expression of p21 [184]. In human colon cancer cells, DIM selectively down-regulated class I HDACs both in vitro and in vivo , which led to inceased expression of p21 and p27 , and induction of DNA damage, resulting in cell cycle arrest in G2 phase and apoptosis, respectively [185].…”
Section: Regulation Of Nutrients On Histone Modification In Cancermentioning
confidence: 99%
“…Both DIM and I3C counteract the effects of enterotoxin B (SEB)-induced activation of T cells in mice as inhibitors of class I HDACs, but not class II HDACs [223]. Notably, DIM, but not I3C, specifically decreases HDAC2 activity in LNCaP and PC-3 prostate cancer cells [224]. Recently, the effects of DIM and SFN on genome-wide promoter methylation have been tested in normal prostate epithelial cells and prostate cancer cells, and the results indicated that DIM reversed abnormal methylation in cancer-associated genes [225].…”
Section: Natural Compounds Alter Epigenetic Modifications Via Epigmentioning
confidence: 99%